Hubungan Antara Faktor Lingkungan Fisik Dengan Perilaku Individu Dengan Kejadian Frambusia Di Puskesmas Biudukfoho Kabupaten Belu - Musu, Yuliana Bita; Setiawan, Budi; Subagiyono, Subagiyono (Jurnal Kesehatan Masyarakat, 2014)
Background: Yaws is caused by a spiral-shaped bacterium is called Treponema pertenue, yaws is infectious diseases in humans and generally attacks the skin and bones. This disease occurs due to environmental circumstances that are poor, the public hasnt been behaving live clean and healthy, the unavailability of an adequate water supply, settlements and infrastructure areas which are less well. Objective: this research aims to know a determine the relationship of physical environmental factors and behaviours of people with yaws in the area of Biudukfoho health centers, Belu Regency, East Nusa Tenggara Province. Method: this type of research is observasional analytic with case control design. Data collection was carried out with the interviews using questionnaire. The Data were analyzed using Chi-Square to find out the values of the Odds ratio and p. value. Results: Analysis statistically bivariat indicates that the variable is associated with yaws in the area of Biudukfoho health centers are the physical environmental factors consists of home conditions include residential (density (OR = 4.19; 95% CI = 1,896-9.272), lighting (OR = 4.89; 95% CI = 2.324-10.317) and the quality of water supply (OR = 7;95% CI = 3701-72.918). Whereas the community behavior (behavior habit of bathing (OR = 2.95; 95% CI = 5.821-1,499), the habit of exchanging towels and clothing (OR = 4.84 (95% C = I-2.393 9.798). Conclusion: physical environmental factors (condition of the home and the quality of the water supply) and behavior (behavior of exchanging towels and clothes) is the risk factors with the occurrence Yaws in Biudukfoho health centers.